Isidore van kinsbergen : (1821-1905) fotopioner en theatermaker in Nederlands- Indie, Photo pioneer and theatre maker in the Dutch East Indies - Boer, Gerda Theuns-de (KITLV Press, 2005)
295 p. : il.; 27 cm